Multi-Strategies for Treating the Roots of Corruption Behavior in Indonesia - Syafruddin Muhtamar; Abdul Rauf; Hardi Hardi (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2022)
Massiveness of corrupt behavior throughout the history of the Republic of Indonesia has had a bad impact on national life and the nation's generation, so it requires comprehensive handling. The purpose of this article is to identify and analyze the root causes of corrupt behavior and determine strategic methods of handling them. The discussion is carried out using a qualitative analysis method, with the support of primary and secondary data. The results of the discussion found that the root of the problem of corrupt behavior is in two influencing factors, namely individual problems and system problems. The individual problem is the loss of awareness of religious values and spiritualism. The system problem is influenced by two factors, namely: civilization dominated by materialism values and the feudal nature of past power. The root of the problem of corrupt behavior can be handled with a multi-strategy approach in the fields of education, culture, politics and law. The fields of education and culture are for the long-term vision and the fields of politics and law for the medium-short-term mission in dealing with the root causes of corrupt behavior. In conclusion, corruption occurs because of weak religious beliefs and individual spiritualism due to the influence of material civilization and feudal character. The replanting of religious and spiritual bases for the nation's generation is very important and forms the basis of a multistrategy approach to dealing with the root causes of corrupt behavior in Indonesia